Unravelling the Dynamics of Madrasah Principal Performance and Teacher Quality: A Literature Review - Jainul Abidin; Fitri Hilmiyati; Anis Zohriah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study investigates teacher quality, principal performance, and the relationship between the two in the madrasa context. The research method uses a literature review. This study's primary and secondary data sources are books and articles from scientific journals. Selection, analysis, synthesis, and interpretation are carried out using this method. The study's findings indicate that the school principal's responsibility is to fulfill his duties and obligations, emphasizing his performance in terms of motivation, knowledge, attitudes, and psychomotor skills. School administrators' total efficacy is reflected in their responsibilities as managers, supervisors, educators, leaders, innovators, and motivators. Effective teaching consists of the following elements: discipline, authority, accountability, charisma, and attitude. In conclusion, the effectiveness of school principals and the caliber of their faculty are critical factors in the development of madrasas. Suggestions state that principal performance and teacher quality should be regularly monitored